2020
DOI: 10.1177/0363546519894333
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Patellar Tendinopathy and Partial Patellar Tendon Tears: A Novel Classification System

Abstract: Background: Patellar tendinopathy is an overuse injury of the patellar tendon frequently affecting athletes involved in jumping sports. The tendinopathy may progress to partial patellar tendon tears (PPTTs). Current classifications of patellar tendinopathy are based on symptoms and do not provide satisfactory evidence-based treatment guidelines. Purpose: To define the relationship between PPTT characteristics and treatment guidelines, as well as to develop a magnetic resonance imaging (MRI)–based classificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 45 publications
(49 reference statements)
1
39
0
Order By: Relevance
“…The most sensitive predictor for the presence of a partial tendon tear in their study was the thickness of the tendon, in which thickness > 8.8 mm was strongly correlated with the presence of a tear. In the present study patients' mean thickness was 12.8 ± 1.1 mm, and in agreement to the latter study we found in all the patients a tendon tear [15]. On MRI images we also found that there was an apparent delay between the observed clinical improvement and the structural repair as shown in the 6 months post-injection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most sensitive predictor for the presence of a partial tendon tear in their study was the thickness of the tendon, in which thickness > 8.8 mm was strongly correlated with the presence of a tear. In the present study patients' mean thickness was 12.8 ± 1.1 mm, and in agreement to the latter study we found in all the patients a tendon tear [15]. On MRI images we also found that there was an apparent delay between the observed clinical improvement and the structural repair as shown in the 6 months post-injection.…”
Section: Discussionsupporting
confidence: 92%
“…The evaluation included the extent of tendinosis and tendon tear. The radiological interpretation was performed by two experienced sports trauma radiologists [15]. Images were reviewed on our institutional picture archiving and communication system (PACS).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Johnson et al reported the MRI findings of patellar tendon thickness in young athletes as being 5.5 mm in asymptomatic individuals and 8.5 mm in patients with patellar tendinosis [ 15 ]. A recent study by Golman et al, which included athletes with or without a partial patellar tendon tear (PPTT) on MRI, showed an average patellar tendon thickness of 5.6 mm in asymptomatic individuals and 10.0 mm in patellar tendinopathy patients with PPTT [ 17 ]. This study also showed similar tendencies for both US and MRI; thus, it is almost certain that tendon thickness is significantly increased in patellar tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…However, these imaging assessments currently lack evidence-based quantitative criteria or classification [ 17 ]. In particular, “thickening of the patellar tendon” is one of the indicators, but there are few articles that have quantitatively defined the thickness at which a tendon should be considered pathological.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the diseased subjects (D1 and D3) had (Popkin-Golman [PG]) grade 3 tendinopathy and one subject (D2) had grade 4 (Table S1). 10 Cells extracted from patients were cultured to passage 2 and subjected to flow cytometry to measure expression of common TPC markers. TPC markers of both healthy and diseased cohorts showed expression of the expected antigen profile CD31 À CD34 À CD45 À CD73 + CD90 + CD105 + (Figure S1B; Table S2), as reported previously.…”
Section: Patient-derived Normal or Tendinopathy Tendon Samples Show Distinct Characteristicsmentioning
confidence: 99%